Synthesis of Sulfonated Chitosan as An Active Agent of Antibacterial Packaging for Fish Fillets - Syahnindita Dyah Ajeng Wartari; Ngadiwiyana Ngadiwiyana; Purbowatiningrum Ria Sarjono; Ismiyarto Ismiyarto; Dwi Susilo (Jurnal Kimia Sains dan Aplikasi, 2024)
Modifying chitosan by increasing its hydrophilic properties through sulfonation reactions will increase its solubility in water and antibacterial activity and expand the application of chitosan. This study aims to determine the antibacterial activity of sulfonated chitosan film applied as fish fillet packaging using the total plate count method. Sulfonated chitosan in this study was successfully synthesized by reacting chitosan with 1,3-propane sultone. Sulfonated chitosan products were characterized using FTIR and UV-Vis spectrophotometers, while antibacterial activity was measured using the disc diffusion method. The optimum temperature for sulfonated chitosan synthesis was 60°C (SCS60). The resulting SCS 60 was a yellowish-white solid soluble in water with a yield of 61.46% and a degree of substitution of 33%. The diameters of the SCS 60 inhibition zone against E. coli and S. aureus isolates were 7 and 10 mm, respectively. SCS60-gelatin film is elastic (elongation 272%) and more hydrophobic with a contact angle of 90.12° compared to chitosan-gelatin film (62.8°). SCC60-gelatin film was able to suppress bacterial growth in fish fillets by up to 0.3 × 104 cfu/g compared to unpackaged fish (30 × 104 cfu/g). Sulfonated chitosan has the potential to be an antibacterial food packaging material.